THE EFFECT OF INTERNAL CONTROL SYSTEM TOWARDS FINANCIAL PERFORMANCE IN PT.KERETA API INDONESIA - Muhamad Gilang Ramadhan Eliada Herwiyanti Eliada Herwiy (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This research is aimed to analyze the influence of internal control on financial performance of PT KAI. This research uses quantitative approach, with multiple linear regression analysis technique. The sampling of the research was done by using purposive sampling technique. Respondents involved in this study were 52 people, consisting of assistant managers and supervisors in PT KAI UPT Balaiyasa Manggarai. The data used is the primary data obtained from the questionnaire.Testing of the hypothesis shows three acceptable hypotheses and two unacceptable ones. The results showed that the control environment, control activities, as well as information and communication have a significant effect on financial performance. While the risk assessment is influential but not significant to the financial performance, while the monitoring has a significant negative effect on financial performance.